Constant glucose biosensor based on vertically aligned carbon nanotube composites - Yousefi, A.T.; Bagheri, Samira; Kadri, Nahrizul Adib; Mahmood, M.R.; Ikeda, S. (Electrochemical Science Group, 2015)
In this contribution, a reagent free glucose biosensor was prepared based on multi walled carbon nanotubes (MWCNTs) composite via the electrochemical method. The synthesized MWCNTs were in turn successfully optimized by the chemical vapor deposition (CVD) method. The glucose oxidase (GOx) was immobilized on a carbon nanotubes/gelatin (Gl) composite using the entrapment technique, with an 8.42 s(-1) direct electron transfer rate between GOx and MWCNTs/Gl, which was then drop-casted onto a glassy carbon electrode (GCE). The bioactivity of GOx on modified GCE was retained during the electrochemical reactions. The cyclic voltammetric results coupled with the chronoamperometric response and obtained from modified GCE indicated that a GOx/MWCNTs/Gl/GC electrode can be utilized as a glucose biosensor via its display of high sensitivity and stability. The biosensor exhibited a wide linearity range to 8.9 mM glucose, with the detection limit of 0.54 mM and a stability of 75.4 current diminish after 25 days. The proposed fabrication method of glucose biosensor was in line with the developments of electrochemical research for glucose determination of human serum in the context of electrochemical reactions. The results indicated that the biosensor possessed good stability and acceptable fabrication reproducibility.